The Inquisition in Brazil: Modus operandi of the inquisitors of the Tribunal of the Holy Office of Lisbon in the processes that involved the colony (1640 - 1739) (2022)
This article deals with the Inquisition in Brazil and the role of the inquisitors in the procedural modus operandi of the ecclesiastical Tribunal of the Holy Office of Lisbon. The source documents indicate part of what was the Portuguese inquisition in Brazil during the colonization process of the territory. It seeks to understand the rite of the process through the actions of the inquisitors, the highest office in the organisation of the Holy Office of the Portuguese Inquisition. With this objective, it was necessary to approach documental sources such as the regulation, the manual for inquisitors and the cases of those accused of various crimes during the Tribunal of Lisbon. Thestudy was realised based on primary sources and illustrated by a case in the colony of Brazil, among many others, providing details about the diverse cases that were judged in the tribunal of the Holy Office of Lisbon, as the Portuguese colony did have its own court yet installed. It is hoped that this study inspires further investigations into the subject with an eye towards studying the most varied processes of the inquisition in Brazil during the colonial period.